HUBUNGAN PERHATIAN ORANG TUA DENGAN KESIAPAN BELAJAR SISWA KELAS III SD NEGERI PORIS PELAWAD 6 - Nasya Uriani Fugri; Mawardi; Hartantri, Saktian Dwi (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to determine the relationship between parental attention and the learning readiness of grade III students of SDN Poris Pelawad 6. The subject of this study is a third grade student of SDN Poris Pelawad 6. The object of this research is the attention of parents and students' learning readiness. This research method uses  an ex-post facto approach  that is correlation and the data used is quantitative data. The population of this study is all participants of classes III A and III B SDN Poris Pelawad 6. The sample in this study amounted to 60 respondents, sampling using the total sampling technique. The data collection technique in this study is in the form of a questionnaire question instrument scale. The hypothesis testing technique uses the Product Moment correlation formula. Before the analysis test, a requirement test was carried out, namely a normality and homogeneity test, a linearity test, a significance test, and a correlation test. Results In this study, r count was obtained 0.618 < r table 1.671, then it can be concluded that H0 is accepted and H1 is rejected at rxy = 0.081 which means that this study has succeeded in testing the correctness of the hypothesis, namely that parental attention does not have a significant relationship with the learning readiness of grade III students at SD Negeri Poris Pelawad 6. Because the correlation coefficient is negative, the lower the parental attention and the lower the student's readiness to learn. With a determination coefficient value of 0.007 indicating the value of R Square 0.007 comes from the quadratic value of the correlation coefficient or "R" which is 0.081 x 0.081 = 0.07 which shows that parental attention contributes to learning readiness by 0.07 x 100 % = 7 %, the remaining 93 % is due to other factors that were not studied in this study. Keywords: Nature of Learning, Learning Theory, Parental Attention, Learning Readiness, Student Characteristics